Heavy Is the Head that Wears the Crown: An Actor-centric Approach to Daily Psychological Power, Abusive Leader Behavior, and Perceived Incivility - Foulk, Trevor A.; Lanaj, Klodiana; Tu, Min-Hsuan; Erez, Amir; Archambeau, Lindy (Academy of Management Journal, 2018)
Recognizing that powerholders operate in dynamic relational and interdependent work contexts, we posit that the effects of psychological power on powerholders are more complex than currently depicted in the literature. Although psychological power prompts behaviors and perceptions that harm the powerless, these reactions are not without consequence for the actor. We integrate the social distance theory of power with consent-based theories of power to posit that, although psychological power elicits negative behaviors and perceptions, these same reactions hurt leaders’ subsequent well-being. To explore this possibility, we conducted an experimental experience sampling study with a sample of managerial employees whom we surveyed for 10 consecutive workdays. We find that leaders enact more abusive behavior and perceive more incivility from others on days when they are exposed to psychological power compared to days when they are not. Leaders higher in agreeableness are less affected by psychological power. In turn, abusive behavior and perceived incivility harm leaders’ subsequent well-being as indicated by their reduced need fulfillment and ability to relax at home. We discuss theoretical implications for research on psychological power, abusive leadership, perceived incivility, and leader well-being, as well as practical implications for employees and their organizations.